Medicines use reviews: a potential resource or lost opportunity for general practice? - Latif, Asam; Pollock, Kristian; Boardman, Helen F. (BioMed Central, 2013)
Background: Patient non-adherence to medicines represents a significant waste of health resource and lost opportunity for health gain. Medicine management services are a key health policy strategy to encourage patients to take medicines as they are prescribed. One such service is the English Medicines Use Review (MUR) which is an NHS-funded community pharmacy service involving a patient-pharmacist consultation aiming to improve patients’ knowledge of medicines and their use. To date the evidence for MURs to improve patient health outcomes is equivocal and GPs are reported to be sceptical about the value of the service. This paper presents the patient’s perspective of the MUR service and focuses on the importance of GP-pharmacist collaboration for patient care. Suggestions on how MURs may have value to GPs through the delivery of increased patient benefit are discussed.